Identity Construction and Transformation of Zen Tourists - Xu Haichao; Liang Zengxian (Redai dili)
Zen culture, a resort within the heritage of Eastern culture, is uniquely expressed through Zen tourism, which blends traditional Chinese culture with travel. This study constructs a theoretical framework of "space-situation-identity" and selects 32 non-religious tourists who participated in Zen tourism for the first time as research samples. Using qualitative methods, this study investigated how non-religious tourists construct and transform their identities through Zen tourism. The findings indicate that motivations for participating in Zen tourism include four dimensions: religious attraction, physical and mental relaxation, emotional connection, and self-discovery. This study constructs the "space-situation-identity" conceptual framework and applies it to Zen tourism. The framework reveals the following insights: "spatial contextualization" and "contextualization of identity" are two stages experienced by Zen tourists, corresponding to identity perception and acquisition, respectively. During these stages, the unique spatial characteristics of Zen tourism sites, regulation and guidance by unofficial organizations, and mutual influence among fellow participants significantly impacted the self-identity transformation and social identity acquisition of Zen tourists. "Identity contextualization" and "contextualization of space" are the two stages when Zen tourists return to the real world, leaving the religious Zen sites, corresponding to individual identity maintenance and identity constraints. In these stages, the identity maintenance of Zen tourists shifts from passive "construction by others" to active "self-construction." This study enriches the research on the identity and role evolution of tourists in religious contexts, emphasizing the need for further exploration of how tourists interact with their environment to form experiences, thereby providing more specific insights and understanding of religious tourism in postmodern society. Furthermore, this study investigates the Zen tourism experiences of non-Zen practitioners in major cities such as Beijing, Shanghai, Guangzhou, and Shenzhen, responding to and expanding existing theories of space, situation, and identity in tourism experiences. It constructs the "space-situation-identity" conceptual framework, highlighting that the identity transformation of Zen tourists involves multiple factors from space and situation, while their new identities influence the elements of space and situation. The interaction between space, situation, and identity is prevalent in various forms of religious tourism across different regions. Similar to this study, most religious sites create a series of sacred contexts through spatial designs and social scene construction. These contexts provide tourists with a new life order and inner meaning, thereby enhancing their religious identities. This study offers several suggestions for optimizing Zen tourism in China. First, organizers should select locations with beautiful natural environments, fresh air, and sites far from urban noise for Zen tourism and improve transportation, accommodation, dining, and wellness facilities to provide comprehensive physical and mental healing services. Second, in addition to experienced Zen instructors, organizers should invite relevant mental health experts to offer professional Zen guidance and psychological counseling to tourists. Third, personalized Zen tourism products should be designed to meet the diverse needs of tourists.